Can we halt health workforce deterioration in failed states? Insights from Guinea-Bissau on the nature, persistence and evolution of its HRH crisis - Russo, Giuliano (2018)
Background: Guinea-Bissau is one of the world's poorest and least developed countries. Amid poverty, political turmoil and state withdrawal, its health workforce (HW) has been swamped for the last four decades in a deepening crisis of under-resourcing, poor performance and laissez-faire. Methods: The present study aimed at analysing the human resources for health (HRH) situation in Guinea-Bissau in light of the recent literature on distressed health systems, with the objective of contributing to understanding the ways health workers react to protracted turmoil, the resulting distortions and the counter-measures that might be considered. Through document analysis, focus group discussions, 14 semi-structured and 5 in-depth interviews, we explored patterns as they became visible on the ground. Results: Since independence, Guinea-Bissau experienced political events that have reflected on the healthcare arena and on the evolution of its health workforce, such as different coup attempts, waves of diaspora and shifting external assistance. The chronic scarcity of funds and a 'stable political instability' have lead to the commercialisation of public health services and to flawed mechanisms for training and deploying health personnel. In absence of any form of governance, health workers have come to own and run the health system. We show that the HRH crisis in Guinea-Bissau can only be understood by looking at its historical evolution and at the wider socio-economic context. There are no quick fixes for the deterioration of HRH in undergoverned states; however, the recognition of the ingrained distortions and an understanding of the forces determining the behaviour of key actors are essential premises for the identification of solutions. Conclusions: Guinea-Bissau's case study suggests that any policy that does not factor in the limited clout of health authorities over a effectively privatised healthcare arena is doomed from the start. Improving health system governance and quality of training should take precedence over expanding HRH. A bloated and ineffective workforce must be managed through incentives rather than administrative orders, in order to improve skills and productivity against higher remuneration and better working conditions. Donor support might be crucial to trigger positive changes, through realistic and sustained investments.